Learning Challenges in Islamic Religious Education: Teacher Strategies and Student Development - M. Basyir Baick; Lathifatul Azizah; Qurrotul Ainiyah; Salma Zahwatul Laili; Suja’iyah Suja’iyah (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2026)
Islamic Religious Education plays a crucial role in fostering students’ religious understanding, moral character, and religious practices. However, various learning challenges continue to hinder the achievement of these educational objectives. This study aims to analyze the learning challenges encountered by students in Islamic Religious Education and examine the strategies employed by teachers to address these challenges at SMP Negeri 2 Mojoagung, Jombang, Indonesia. The study employed a qualitative descriptive approach. Data were collected through semi-structured interviews, classroom observations, and documentation involving Islamic religious education teachers and eighth-grade students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings revealed that students experienced multidimensional learning challenges, including difficulties in understanding Islamic Religious Education materials, limited Qur’anic literacy skills, inconsistent religious practices, and low learning motivation. To address these challenges, teachers implemented several strategies, including creating supportive learning environments, providing additional Qur’anic literacy guidance, applying motivational reinforcement and reward-based approaches, and monitoring students’ religious practices through parental involvement. The findings indicate that learning challenges in Islamic religious education are interconnected and require comprehensive pedagogical responses that integrate cognitive, behavioral, and motivational dimensions. This study contributes to the literature on Islamic religious education by offering a holistic understanding of learning challenges and teacher strategies within a public junior high school context. The findings also provide practical implications for educators seeking to enhance the quality of Islamic religious education through more adaptive and student-centered approaches.